Simultaneous removal process for humic acids and metal ions by adsorption - Terdkiatburana, Thanet (Curtin University, 2007)
Humic substances are macromolecules that naturally occur in all environments in which vegetation matter are present. In general, humic acid is part of humic substances which form the major fraction of the dissolved organic matters in surface water and represents 90% of dissolved organic carbon. Humic acid plays a fundamental role in many ecosystems since it interacts with toxic metal ions present in the system, resulting in a decrease in the bio-availability of such ions. Moreover, the availability of humic acid in water can react with other chemical compounds, such as chlorine to form trihalomethanes (including chloroform) and causes an increasing risk of cancer and may be linked to heart, lung, kidney, liver, and central nervous system damage. Therefore, humic acid removal in water treatment processes is very important in order to achieve the drinking water standards. Heavy metals are significant contaminants in aqueous system. All heavy metals can produce toxicity when ingested in sufficient quantities, but there are several important ones such as lead, mercury, copper, cadmium, arsenic, nickel and silver. These heavy metals are so pervasive and produce toxicity at low concentrations. Moreover, they may build up in biological systems and become a significant health hazard.Adsorption is approved as an effective and simple method for water and wastewater treatment process. Many adsorbents then are developed for use in adsorption process such as montmorillonite, peat, activated carbon, etc. In this research, humic acid and heavy metals were mainly selected for adsorption study. In the sorption experiment, several adsorbents such as synthesised zeolite (SZ), natural zeolite (NZ), powdered activated carbon (PAC) and fly ash (FA), were selected to examine the application of HA and heavy metals both in individual and simultaneous adsorption, The characteristics and interactions of the adsorbents with HA and heavy metals were systematically studied by batch laboratory experiments. In the beginning, the adsorption of HA onto SZ, NZ, PAC and FA was investigated and their adsorption capacity was compared. The equilibrium adsorption of HA on SZ, NZ, PAC and FA was found to be 84.1, 67.8, 81.2 and 34.1 mg/g, respectively, at 30 oC and pH 5.0. Dynamic adsorption data show that these adsorbents could reach their adsorption equilibrium after 50 hours. From pH analysis, HA adsorption is favoured at low pH and an increase in pH will lead to the reduction of HA adsorption. SZ and NZ adsorption capacity were affected by the changing of solution temperature; however, in PAC and FA sorption study, there was no significant effect observed. Two heavy metal ions (Cu, Pb) removal by the adsorbents was then conducted. The results showed that the equilibrium sorption capacity of Cu and Pb ions on SZ, NZ, PAC and FA were 43.5, 24.2, 19.7, 28.6 and 190.7, 129.0, 76.8 mg/g, respectively at 30 oC and a pH value of 5. The appropriate pH for Cu and Pb removal was found to be 5 and 6. In most dynamic cases, these adsorbents needed at least 50 hours to reach the adsorption equilibrium. Only adsorption on FA required more than 150 hours to reach the equilibrium.In simultaneous adsorption experiments, the influences of HA and heavy metal concentration (in the range of 10 to 50 mg/L for HA and 10 to 30 mg/l for heavy metals) on the HA-heavy metal complexation were investigated. The results demonstrated that increasing HA concentration mostly affected Cu adsorbed on SZ, FA and PAC and Pb adsorbed on SZ, NZ and PAC. For HA adsorption, the adsorption rate decreased rapidly with increased initial metal ion concentration. Moreover, the adsorption of heavy metals increased with increased heavy metals concentration in the presence of HA. In the presence of heavy metal ions, the order of HA adsorption followed PAC > FA > SZ > NZ. According to the results, the individual and simultaneous adsorption of HA and heavy metals on each adsorbent achieved a different trend. It mainly depended on the adsorption property of both adsorbates (HA and heavy metals) and adsorbents (SZ, NZ, PAC and FA) and also the operation factors such as pH, concentration, temperature and operation time. Even though this experiment could not obtain high adsorption performance, especially in coadsorption, as compared with other adsorbents, the adsorbents in this study represented a higher adsorption capacity and provide the potential for further development.